Consumer Risks in Fintech : New Manifestations of Consumer Risks and Emerging Regulatory Approaches - World Bank (World Bank, Washington, DC, 2021)
Fintech is increasingly recognized as a key enabler for financial sectors worldwide, enabling more efficient and competitive financial markets while expanding access to finance for traditionally underserved consumers. A critical challenge for policy makers is to harness the benefits and opportunities of fintech while managing its risks, including for consumers. The COVID-19 pandemic further accelerated the widespread transition of consumers to fintech and digital financial services, highlighting their significant benefits while also demonstrating how risks to consumers can increase in times of crisis and economic stress. This paper (1) identifies a range of consumer risks posed by fintech, focusing on four key fintech products (digital microcredit, peer-to-peer lending, investment-based crowdfunding, and e-money) and (2) discusses consumer protection regulatory approaches emerging internationally for policy makers to consider when developing regulatory policy to target such risks. Examples of regulatory approaches are drawn from country examples and international literature. The paper also discusses a range of implementation considerations.